2020
DOI: 10.34128/jtai.v7i1.115
|View full text |Cite
|
Sign up to set email alerts
|

Kesetimbangan Adsorbsi Zat Warna Metilen Blue dengan Adsorben Karbon Aktif Tongkol Jagung Terimpregnasi Fe2O3

Abstract: Methylene blue merupakan zat warna organik yang banyak digunakan pada industri tekstil, memiliki sifat mudah larut dalam air dan berbahaya bagi kesehatan manusia. Pada penelitian ini, adsorbsi zat warna metilen blue dilakukan dengan menggunakan adsorben karbon aktif dari tongkol jagung yang terimpregnasi Fe2O3. Proses adsorbsi dijalankan pada sebuah reaktor batch selama 120 menit dengan menggunakan adsorben KAJ/Fe2O3 sebanyak 0,025 gram dan kecepatan pengadukan 150 rpm. Tujuan penelitian ini adalah untuk mempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research conducted by Baunsele and Missa (2020), using Fe2O3 impregnated corncob activated carbon adsorbent is available Langmuir isotherm with Langmuir constant and adsorption capacity/the maximum (qm) obtained were 0.49 and 15.38 mg/L, respectively. The research using coconut coir adsorbent showed that the adsorption of methylene blue using coconut coir adsorbent followed the model pseudo second order reaction kinetics with adsorption constant rate of 0.01 gram mg -1 minute -1 (Ristianingsih et al, 2020). This indicates that the absorption capacity of methylene blue by CHMFKR is greater.…”
Section: Adsorption Isothermmentioning
confidence: 89%
“…Research conducted by Baunsele and Missa (2020), using Fe2O3 impregnated corncob activated carbon adsorbent is available Langmuir isotherm with Langmuir constant and adsorption capacity/the maximum (qm) obtained were 0.49 and 15.38 mg/L, respectively. The research using coconut coir adsorbent showed that the adsorption of methylene blue using coconut coir adsorbent followed the model pseudo second order reaction kinetics with adsorption constant rate of 0.01 gram mg -1 minute -1 (Ristianingsih et al, 2020). This indicates that the absorption capacity of methylene blue by CHMFKR is greater.…”
Section: Adsorption Isothermmentioning
confidence: 89%
“…One common method to reduce dye pollution is adsorption. Adsorption is cost-efficient and ecofriendly because the materials used can come from natural samples or environmental waste, and this method is easier to do, has high efficiency, and is widely used [9,10].…”
Section: Introductionmentioning
confidence: 99%